Early childhood caries: Epidemiology, severity and sociobehavioural determinants - Moimaz, Suzely Adas Saliba [UNESP]; Borges, Heloisa Carvalho [UNESP]; Saliba, Orlando [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2016)
Purpose: To investigate the association between sociobehavioural variables and the pattern and severity of early childhood caries in Brazilian infants and toddlers ages 0-3 years. Materials and Methods: This was a cross-sectional study with 768 children who attended 58 public nursery schools. Five previously calibrated teams (Kappa = 0.842) performed oral examinations, using the decayed, missing, filled teeth (dmft) index according to the WHO methodology. A pretested, self-administered questionnaire was given to the subjects' parents or guardians to obtain sociobehavioural information. Results: Caries was observed in 134 of the 768 (17%) children. Caries and rampant caries were significantly more prevalent in low-income families (p = 0.0121) and the incidence of caries was associated with access to dental services (p < 0.05). The percentages of children who were caries free in the age groups of 0-11 months, 12-23 months, 24-35 months and 36-47 months were 100%, 96%, 88% and 76%, respectively. Conclusion: Programmes for prevention and oral health education should be instituted, preferably during the first year of life, especially for those in the most socioeconomically deprived groups.
Keywords: Dental caries; Epidemiology; Primary dentition